THE PLACE OS PRACTICE IN INITIAL TEACHER EDUCATION: LOCATING THE CONCEPT OF PRACTICAL PREPARATION IN CONTEXTS OF INSERTION TO TEACHING IN BRAZIL - Amorim Tamaio de Souza, Nathalia Cristina [UNESP]; Guarnieri, Maria Regina [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
From a discussion that focuses the inefficiency of conventional modes of insertion to teaching in Brazil, this article aims to presents a relatively new concept and its potential to rethink the time allowed to practice in initial teacher education. This is the concept of practical preparation, based on the contributions of Marcelo, Gauthier et al. and Gimeno. The research carried out, of theoretical nature, has as central indicator the need of the training courses to review their insertion to teaching strategies, guided into an insertion organic template that provides the future teacher, through practical interventions organized, a consistent preparation for the beginning of the teaching profession.
Keywords: Initial teacher education; Insertion to teaching; Practical preparation